Coconut & sambal : recipes from my Indonesian kitchen - Lee, Lara (Bloomsbury, 2020)
Beyond Indonesia's lush rainforests, tropical seas and abundant rice fields lies a country not often seen by visitors. It is one of bustling local markets, lively street food stalls, colourful shops and houses and generous community spirit. From these islands comes one of the most diverse cuisines in the world, weaving flavours of lemongrass, chilli, tamarind and coconut into dishes that are fragrant, colourful and bold. Australian-born chef Lara Lee takes us on a journey to trace her family's Indonesian roots, and in the kitchens of her grandmother and extended family, she discovers the secrets to real Indonesian cookery. Now she shares more than 80 authentic, mouth-watering recipes that have been passed down through the generations, so you can recreate dishes such as Nasi goreng, Beef rendang, Chilli prawn satay and Pandan cake. There are also recipes for a variety of sambals: fragrant, spicy relishes - ranging from mild to fiery - that are undoubtedly the heart and soul of every meal. The recipes in Coconut & Sambal use easily accessible ingredients and simple techniques and are interwoven with beguiling tales of life on the islands and vibrant food and travel photography, shining a light on the magnificent but little-known cuisine of Indonesia.